Analysis and Design of Information System Sales Report PT. Akses Komunikasi Indonesia Web-Based - Yanto Setiawan; Ardiansyah Eka Pradista; Al Hamim Muharram (Syntax Corporation, 2022)
The purpose of making this thesis is to provide solutions to the problems of PT. Access Komunikasi Indonesia for control and ensure product marketing activities can run according to the target and able to provide reports in real time as well as make it easier for employees to access them. The data collection method used to obtain user needs is the method of observation, interviews and literature study. The technology that we use for building this website is Laravel framework, Angular JS, and Database using MySQL. The development method used is SDLC Model. The conclusion of this thesis is that the existence of a web-based sales report system is expected to help PT. Akses Komunikasi Indonesia for getting product marketing reporting results easily, quickly, and accurately.